Quantitative analysis of protein-protein interactions and post-translational modifications in rare immune populations. Issue 1 (December 2017) - Avin, Ayelet; Levy, Maayan; Porat, Ziv; Abramson, Jakub
Abstract In spite of recent advances in proteomics, quantitative analyses of protein–protein interactions (PPIs) or post-translational modifications (PTMs) in rare cell populations remain challenging. This is in particular true for analyses of rare immune and/or stem cell populations that are directly isolated from humans or animal models, and which are often characterized by multiple surface markers. To overcome these limitations, here we have developed proximity ligation imaging cytometry (PLIC), a protocol for proteomic analysis of rare cells. Specifically, by employing PLIC on medullary thymic epithelial cells (mTECs), which serve as a paradigm for a rare immune population, we demonstrate that PLIC overcomes the inherent limitations of conventional proteomic approaches and enables a high-resolution detection and quantification of PPIs and PTMs at a single cell level. Rare immune or stem cell populations are difficult to quantitatively analyze for protein-protein interactions or post-translational modifications despite advances in proteomics. Here the authors develop proximity ligation imaging cytometry for high-resolution detection at a single cell level.